Pengelolaan terhadap Lingkungan dalam Perspektif Quraish Shihab - Humrotus Safataeni; Hanifatul Azizah; Aang Ahmad Syahid; Ahmad Mumtazul Faqih; Andi Rosa (Pusat Riset dan Inovasi Nasional, 2025)
The global environmental crisis demands a comprehensive approach, including from a religious perspective. Islam as a religion that is very holistic contains teachings about nature conservation which are unraveled in the Qur'an. However, the study of contemporary mufasir's views on environmental issues is still very limited, especially in the context of the thought of Prof. Dr. M. Quraish Shihab. This article also aims to examine how in the view of quraish shihab about the importance of environmental preservation in life. on the principles of environmental management reflected in his interpretation, as well as his contribution in providing solutions to problems in the current environment. In addition, this article will discuss a comparison of the approach of the interpretation of the Qur'an Shihab with other contemporary scholars, such as for example in the Tafsir of Al Azhar by Hamka. This study uses a qualitative method with a holistic thematic interpretation (maudhui) approach and a systematic approach to scientific interpretation. The results of the study show that Quraish Shihab views the environment as a mandate from Allah swt that we must maintain its sustainability with the principles of balance, sense of responsibility, and sustainability. His relevant thinking is to be used as the basis for Islamic environmental ethics that are applicable in the modern era. This finding also fills the literary gap in the study of contemporary interpretation by presenting ecological solutions based on the Qur'an.